Exploring Trust, Privacy, and Security in Cloud Storage Adoption among Generation Z: An Extended TAM Approach - Rio Guntur Utomo; Rahmat Yasirandi (Kinetik Game Technology Information System Computer Network Computing Electronics and Control, 2024)
The incorporation of cloud storage technology holds the promise of significantly enhancing efficiency in various sectors, particularly from the perspective of Generation Z, a demographic known for its meticulous consideration of technology acceptance factors, especially security. This research thoroughly examines the level of acceptance of cloud storage technology among Generation Z. By augmenting the Technology Acceptance Model (TAM) with five core factors and introducing three novel factors—Perceived Security, Perceived Privacy, and Trust—this study not only adheres to traditional acceptance models but also ventures into uncharted territories, marking a significant contribution to understanding technology acceptance. This study meticulously collected data from 408 Generation Z respondents who actively use cloud storage technology, employing an innovative questionnaire disseminated via an online platform. Through sophisticated PLS-SEM data analysis, the study confirmed the positive and significant impact of all tested hypotheses, underscoring the importance of attitudes, perceived benefits, and usability in fostering the intention to use cloud storage. Notably, the added dimensions of privacy and security emerged as critical in enhancing users' trust in cloud storage solutions. Furthermore, this study paves the way for future explorations into technology acceptance across diverse populations and settings, underscoring the critical role of security and privacy in shaping technology adoption decisions among emerging generations.
Keywords: Blockchain Technology Applications and Security; FinTech, Crowdfunding, Digital Finance; Privacy-Preserving Technologies in Data